To find the solution for the system of equations \(y = 2x - 5\) and \(y = x - 3\) using the table provided, we need to find the point \((x, y)\) where the outputs for both equations are equal (i.e., when both equations yield the same \(y\) value for a given \(x\)).
From the table:
-
For \(x = 0\):
- \(y = 2(0) - 5 = -5\)
- \(y = 0 - 3 = -3\)
-
For \(x = 1\):
- \(y = 2(1) - 5 = -3\)
- \(y = 1 - 3 = -2\)
-
For \(x = 2\):
- \(y = 2(2) - 5 = -1\)
- \(y = 2 - 3 = -1\) (this is a match)
-
For \(x = 3\):
- \(y = 2(3) - 5 = 1\)
- \(y = 3 - 3 = 0\)
Since the only point where both equations yield the same \(y\) value occurs when \(x = 2\) (with both equations giving \(y = -1\)), the solution for this system of equations is:
\((2, -1)\)
Therefore, the correct response is:
(2,−1).